Rab11-FIP1/RCP Functions as a Major Signalling Hub in the Oncogenic Roles of Mutant p53 in Cancer - von Grabowiecki, Yannick; Phatak, Vinaya; Aschauer, Lydia; Muller, Patricia A. J. (Frontiers in Oncology, 2021)
Rab11-FIP1 is a Rab effector protein that is involved in endosomal recycling and trafficking of various molecules throughout the endocytic compartments of the cell. The consequence of this can be increased secretion or increased membrane expression of those molecules. In general, expression of Rab11-FIP1 coincides with more tumourigenic and metastatic cell behaviour. Rab11-FIP1 can work in concert with oncogenes such as mutant p53, but has also been speculated to be an oncogene in its own right. In this perspective, we will discuss and speculate upon our observations that mutant p53 promotes Rab11-FIP1 function to not only promote invasive behaviour, but also chemoresistance by regulating a multitude of different proteins.